Effect of Nonverbal Communication in English Classes - Kshetree, Arun Kumar (Vox Batauli, 2023)
This paper has been prepared on the basis of the study to find out the different kinds of nonverbal communications in English classes of secondary level students. It was prepared with the aim of investigating the effect of nonverbal clues of the teachers in teaching English. Forty students of grade ten from four different schools of Butwal Sub-metropolitan city were asked some questions related to the nonverbal communication and nonverbal behaviours of the teachers and their impact on the students specially focusing on the English teachers and their classes. From the data gathered it was found out that the non verbal communication is very common and important in English classes and in many cases it supports the students in getting meanings of different expressions of the teachers and helps them to get motivated in learning English. One thing of caution is that the non verbal behaviours are much culture bound and the teachers need to be aware of the cultural background of the students. The findings and conclusions of this study will help the teachers improve their teaching by being conscious to their non verbal signals while teaching and reacting to the students' behaviours in the class and in the school.